USE OF BLUE LED LIGHTS AS AN ATTRACTANT IN A COLLAPSIBLE POT ON BLUE SWIMMING CRAB CATCHES - Prasetyo Aji, Bagus; Mawardi, Wazir; Fuad, Fuad; Riyanto, Mochammad (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2025)
Blue light-emitting diode (LED) lights have been tested as a potential tool in a blue swimming crab collapsible pot at the laboratory level. However, field-scale trials have not yet been conducted to confirm their effects on pot catches. This study aims to determine the effects of blue LEDs on catch composition and the effectiveness of catching the main target of crab (Portunus pelagicus). A fishing trial was conducted in Brondong, Lamongan waters to examine the influence of blue LED lights on crab catches. A total of 54 pots were deployed, consisting of 18 pots with fish bait (U) as control, 18 pots with blue LED light (L), and 18 pots with a combination of fish bait and blue LED (LU). The results showed that the LU treatment yielded the highest number of species, with a total of 13 species, followed by the U treatment, with 10 species, and the L treatment, with 9 species. The LU treatment had the highest catch of 48 fish (3,718 g), followed by U with 43 fish (3,448 g) and L with 5 fish (208 g). Statistical analysis revealed no significant differences between the LU and U (control) treatments in terms of both catch number and weight. The highest catchable width distribution in treatment U was 88%, while the highest catchable weight distribution in treatment LU was 75%. The analysis of crab-catching effectiveness analysis showed that the LU treatment had the highest average effectiveness of 13%, followed by the U treatment at 11%, and the lowest was the L treatment at 1%. In conclusion, LED lights do not affect the catch, however, adding LED lights to the bait can increase the number of species caught, the number of individuals, the weight of the catch, and the effectiveness of catching kingfish (P. pelagicus). Keywords: Blue light, catchable distribution, effectiveness, bait